2008
DOI: 10.1186/1471-5945-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Melasma and its association with different types of nevi in women: A case-control study

Abstract: Background: Very little is known about possible association of nevi and melasma. The study objective was to determine if there is an association between melasma and existence of different kinds of nevi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Recent research findings have highlighted the important role of hormones in the pathogenesis of acne. Androgens are believed to contribute to the development of acne, and this theory strengthens more when considering the interactions between sebum production, hirsutism, polycystic ovarian disease, and melasma with acne and androgens 37. Considering the pathophysiology of acne, newer steroid-related therapies need to be identified and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research findings have highlighted the important role of hormones in the pathogenesis of acne. Androgens are believed to contribute to the development of acne, and this theory strengthens more when considering the interactions between sebum production, hirsutism, polycystic ovarian disease, and melasma with acne and androgens 37. Considering the pathophysiology of acne, newer steroid-related therapies need to be identified and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary factor may play a role in the causation of melasma. Positive family history of melasma is reported in several studies 26,[30][31][32][33] . Although genetic influence is suggested by a twin study, it is not generally accepted 34,35 .…”
Section: Discussionmentioning
confidence: 87%
“…The results of Passeron et al 25 are in concordance with our study. Approximately 10% of Caucasian patients with melasma, 26% of Indian patients with melasma, 4% of Korean patients with melasma, and 14.5% of Latino patients with melasma were men in the literature [26][27][28] . Sun exposure was the strong aggravating factor in both the groups of patient (86.67% of total patients).…”
Section: Discussionmentioning
confidence: 99%
“…Hassan Adalatkhah et al found that existence of some types of nevi specially the lentigenes and melanocytic nevi increase the chance of melasma. 18 Associated dermatological conditions can be attributed to the common etiological factors like sun exposure and hormonal imbalance.…”
Section: Discussionmentioning
confidence: 99%